KEPATUHAN IMUNISASI TT ; SURVEY PADA IBU HAMIL DI UPTD PUSKESMAS NAPAGADUNG LAUT KABUPATEN PADANG LAWAS SUMATERA UTARA - Samsuriana; Utama, Indra; Brahmana, Netti Etalia; Sembiring, Rinawati; Etty, Christina Roos; Sipayung, Apriska Dewi (UNIVERSITAS SARI MUTIARA INDONESIA, 2022)
The Compliance on pregnant women to do TT Immunization are pregnant women who want to receive TT Immunization at least twice during pregnancy to do of preventing infection during pregnancy, birth, and, puerperium. This study is qualitative research to know how to compliance women pregnant to do implementing TT immunization at UPT Napagadung Laut health center, North Padang Lawas. Participation in this study is pregnant women with ten participants, the head of the Health Center, the coordinator of midwifery, and fifth a village of midwifery with a purposive sampling technique. The result of this study is a majority that of pregnant women is not understood TT immunization and the benefits of immunization for pregnant women, support by husbands is very low, and participants of village midwifery always support pregnant women to receive TT immunization, access is very low and far healthcare facilitation, the head of the center provides facilities and infrastructure support, SOP of TT immunizes already existed exists and has been socialized and health caders to do not play an active role to implementation of posyandu activities, especially the implementation of TT immunization for pregnant women. This research is expected to be a reference for the further researcher to develop higher research as well as a material consideration for practitioners, especially for policy macer to improve the compliance of pregnant women to do TT immunization.